2013
DOI: 10.1111/1471-0528.12290
|View full text |Cite
|
Sign up to set email alerts
|

Provision of long‐acting reversible contraception in HIV‐prevalent countries: results from nationally representative surveys in southern Africa

Abstract: Objective To analyse the current provision of long-acting reversible contraception (LARC) and clinician training needs in HIV-prevalent settings. Design Nationally representative survey of clinicians. Setting HIV-prevalent settings in South Africa and Zimbabwe. Population Clinicians in South Africa and Zimbabwe. Methods Nationally representative surveys of clinicians were conducted in South Africa and Zimbabwe (n = 1444) to assess current clinical practice in the provision of LARC in HIV-prevalent sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 16 publications
(22 reference statements)
1
38
2
1
Order By: Relevance
“…This finding may be due to low awareness of the safety of long‐acting reversible contraceptives among HIV‐positive women [18] and their health provider. Further studies are necessary to confirm this assumption; however, Morse et al [24] have reported that the clinician's perception that the IUD and implant are inappropriate for HIV‐positive women, despite evidence to the contrary, might affect usage.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due to low awareness of the safety of long‐acting reversible contraceptives among HIV‐positive women [18] and their health provider. Further studies are necessary to confirm this assumption; however, Morse et al [24] have reported that the clinician's perception that the IUD and implant are inappropriate for HIV‐positive women, despite evidence to the contrary, might affect usage.…”
Section: Discussionmentioning
confidence: 99%
“…Many practitioners who are unaware of WHO medical eligibility criteria for contraceptive use also make inappropriate contraception prescriptions for diseases other than epilepsy [3,5,6,24]. A cross‐sectional study using a UK general practice research database [5] demonstrated that the percentage of women with high cardiovascular risk using inappropriate contraception was only slightly reduced over time (from 8.1% in 2004 to 7.3% in 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of unplanned pregnancy among women with comorbidities—e.g. infection with HIV or a history of thrombosis—are even higher, because many doctors are unaware of WHO medical eligibility criteria for contraceptive use [2] and therefore prescribe inappropriate or poorly effective contraceptive methods for these women [3–6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, although IUDs are highly effective contraceptive methods, a previous analysis showed very few providers reported that either the copper or levonorgestrel-releasing IUD was appropriate for at-risk or HIV positive women [10], despite data showing they are safe and acceptable among both groups of women [15–17]. Encouragingly South Africa’s newly-released contraception guidelines emphasize long-acting methods, and the National Department of Health is moving forward with a national contraceptive implant introduction and revitalization of the IUD [18–20].…”
Section: Discussionmentioning
confidence: 99%
“…The surveys were pilot tested in each country for content and comprehension, and the final instrument covered professional training, practice setting, patient population, and provider knowledge, attitudes and clinical practices. The methods have been described in detail previously [8,10]. …”
Section: Methodsmentioning
confidence: 99%